Mutations in CCBE1 cause generalized lymph vessel dysplasia in humans - Alders, Marielle; Hogan, Benjamin M; Gjini, Evisa; Salehi, Faranak; Al-Gazali, Lihadh; Hennekam, Eric A; Holmberg, Eva E; Mannens, Marcel M A M; Mulder, Margot F; Offerhaus, G Johan A; Prescott, Trine E; Schroor, Eelco J; et al. (Nature genetics, 2009)
Raoul Hennekam and colleagues report the identification of mutations in CCBE1 that cause Hennekam syndrome in humans. Features of Hennekam syndrome include lymphedema, lymphangiectasias, mental retardation and unusual facial characteristics. CCBE1 encodes Collagen and Calcium-Binding EGF domain-1, a secreted protein that has been shown to be required for embryonic lymphangiogenesis in zebrafish. Lymphedema, lymphangiectasias, mental retardation and unusual facial characteristics define the autosomal recessive Hennekam syndrome. Homozygosity mapping identified a critical chromosomal region containing CCBE1 , the human ortholog of a gene essential for lymphangiogenesis in zebrafish. Homozygous and compound heterozygous mutations in seven subjects paired with functional analysis in a zebrafish model identify CCBE1 as one of few genes causing primary generalized lymph-vessel dysplasia in humans.